PENGARUH KONDISI SOSIAL EKONOMI DAN LATAR BELAKANG PENDIDIKAN ORANG TUA TERHADAP MOTIVSI BELAJAR SISWA DI SMK NEGERI 1 KEMPAS INDRGAIRI HILIR - Dewi wahyu lestari; Caska Caska; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the influence of the socio-economic conditions and educational background of parents on the learning motivation of students of SMK Negeri 1 Kempas Indragiri Hilir. The population in this study were students of SMK Negeri 1 Kempas. This number cannot be determined. The sampling technique uses the simple random sampling method, which is a way to identify, select and take samples in a continuous network or chain of relationships until the number of samples in this study is 100 respondents. The data analysis used is the prerequisite test that has been carried out by the SPSS Statistics Version 22 program. The results of the study stated that 1) the socio-economic conditions had a positive and significant effect on student learning motivation, 2) the educational background of parents had a positive and significant effect on student learning motivation, 3) the socioeconomic conditions and educational background of parents had a positive and significant effect on Student's motivation to study.Keywords: Socio-Economic Conditions, Parents Background, Learning Motivation